Biomarcadores endoteliais como preditores de óbito após infecção pelo Sars-Cov-2 em transplantados de órgãos - Lima, Paula Roberta de (2023)
Introduction: SARS-CoV-2 infection (Covid-19) poses a significant threat to immunosuppressed patients, resulting in elevated morbidity and mortality rates. To effectively manage the care of these patients, the use of outcome predictor tools is crucial. Biomarkers, among the predictive variables, play a vital role in predicting mortality in immunocompetent patients. This study aimed to assess the predictive capacity of endothelial injury biomarkers in solid organ transplant (SOT) patients hospitalized due to Covid-19. Methods: A prospective cohort study was conducted, including SOT recipients from two transplant services in Fortaleza, Ceará, who were hospitalized for Covid-19 between July 2020 and July 2021. Eligible patients were those with a positive RT-PCR for SARS-CoV-2 and required hospitalization for Covid-19. Endothelial injury biomarkers, including VCAM-1, syndecan-1, and angiopoietins 1 and 2 (ANG-1 and ANG-2), were evaluated at the time of hospital admission. Patients were followed for three months after the diagnosis of Covid-19. Results: The sample included 52 patients, with 59.6% being men, and a mean age of 56 ± 14 years. The majority of patients were long-term kidney transplant recipients (76.9%), with a median transplantation duration of 6 years (interquartile range: 1-11 years). Among the patients, 29 (55.8%) died. There were no significant differences in ANG-1 biomarker levels (64.0 ± 13.7 vs. 60.2 ± 16.9 ng/mL, p=0.392), VCAM-1 (2721 ± 865 vs. 2933 ± 1281 ng/mL, p=0.501), and syndecan-1 [343.0 (interquartile range: 113.6-463.0) vs. 515.2 (interquartile range: 173.0- 4102.3) ng/mL, p=0.194] between the groups of surviving and deceased patients. However, mean ANG-2 values (3.8 ± 2.3 vs. 6.0 ± 3.4 ng/mL, p=0.012), as well as the ANG-2/ANG-1 ratio (0.06 vs. 0.08, p=0.009), were significantly higher in patients who died. In the multivariate cox regression analysis, to independently assess the association with mortality, syndecan-1 was related. Patients who were admitted with syndecan-1 levels > 720ng/mL had a hazard ratio of 10.9 (95% CI: 2.428 – 49.344). Conclusion: Elevated levels of Angiopoietin-2 were associated with mortality in hospitalized solid organ transplant patients with Covid-19.